Recent Advances and Challenges in 2D Metal-Free Electrocatalysts for N2 Fixation - Xia, Xinyuan; Li, Bin; Liu, Shanshan; Tang, Bo (Frontiers in Chemistry, 2020)
The ever-growing requirement of ammonia for industry and energy supply motivates people to find clean and cost-effective alternatives to overcome the shortcomings of the century-old Haber-Bosch process. Electrocatalytical N2 reduction (NRR) is considered as a prospective way for ammonia production at ambient conditions. Recently, two-dimensional (2D) metal-free materials are emerging as highly efficient and robust electrodatalysts for NRR owing to their advanced features: highly exposed surface, abundant active sites, tunable electronic states, and long-term stability, compared to metal-based and bulk catalysts. In this minireview, we briefly summarize the latest edge reports on 2D metal-free materials catalyzed NRR. Also, we discuss the challenges and perspectives on the design and synthesis of novel 2D metal-free catalysts.